قاعدة القادر على اليقين هل يأخذ بالظن: حقيقتها وتطبيقاتها - الرشيد، أحمد بن عبدالرحمن بن ناصر (الأمانة العامة لهيئة كبار العلماء, 2020)
المقصود بالقاعدة: أن القادر على الحصول على الحكم بطريق قطعي هل يجوز له تركه والاكتفاء بطرق أخرى محتملة للصواب أكثر من الخطأ؟ وقد وردت القاعدة بصيغ متعددة عند أهل العلم، أغلبها ورد بصيغة الخبر الدال على حكم القاعدة دون إشعار بالخلاف فيها، وبعضها ورد بصيغة الاستفهام المشعرة بالخلاف في القاعدة. والعلماء مختلفون في حكم القاعدة، والذي ترجح للباحث: أن القادر على اليقين يجوز له العمل بالظن، إلا إذا كان اليقين قريبًا من التحقق دون تعب كثير، فيجب العمل به حينئذٍ؛ لأنه كاليقين المتحقق، وهذا الحكم العام للقاعدة لا يصح تطبيقه بمفرده على جميع الفروع المترددة بين الظن واليقين، بل يجب الاجتهاد في كل فرع بحسبه. وقد دل الكتاب العزيز والسنة المطهرة والاعتبار الصحيح على حجية القاعدة ومشروعية بناء الأحكام عليها، إذا توافرت الشروط الآتية: -أن يكون الظن معتبرًا. -ألا يكون اليقين متحققًا في المسألة. -ألا يمكن تحصيل اليقين إلا بمشقة. -ألا تكون القدرة على اليقين بعد حصول المقصود من العمل بالظن. وللقاعدة تطبيقات أصولية مهمة، كما أن لها تطبيقات فقهية كثيرة، ولذا فهي من القواعد الأصولية الفقهية.
This rule refers to the idea that whoever can reach a certain ruling; can he forsake it and go for other probable solutions that are more likely true? The rule was mentioned in different wording by scholars. The most frequently used form is that related in a statement form indicating the ruling without discussing the differences about it; some forms are reported in a question form that imply differences. Scholars differ about the ruling but the most likely weighty position according to the author of this paper is that whoever is certain of an issue may incline uncertainty except that certainty is almost achievable effortlessly, then he has to abide by it. Forsake it and go for other probable solutions that are more likely true? This can not be generalized in its own right on all issues that fluctuate between certainty and uncertainty, but due diligence must be pursued in every case. Textual evidence from the Qur’an and Sunnah in addition to correct personal judgment indicated the validity of the rule and legality of using it as a basis for rulings if the following conditions are met: - Justifiable certainty. - Certainty is not about to take place. - Certainty cannot be reached easily. - Ability to reach certainty after the achievement of the intended objective should not be attained by uncertainty. The rule has significant theoretical applications in jurisprudence; therefore, it is considered one of the theoretical jurisprudential rules.
Keywords: الفقه الإسلامي -- الأحكام الشريعية -- علم الأصول -- المذاهب الإسلامية